2016
DOI: 10.1158/2326-6066.cir-15-0118
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Random Healthy Donor–Derived Allogeneic Natural Killer Cell Therapy in Patients with Malignant Lymphoma or Advanced Solid Tumors

Abstract: Natural killer (NK) cells with mismatched killer cell immunoglobulin-like receptor-ligand pairs have shown efficacy and been proven safe in treatment of cancer patients. Ex vivo-expanded and highly activated NK cells (MG4101) had been generated under good manufacturing practice conditions, which demonstrated potent anticancer activity in vitro and in vivo in preclinical studies. The current phase I clinical trial was designed to evaluate safety and possible clinical efficacy of repetitive administrations of MG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 49 publications
0
103
0
Order By: Relevance
“…In our previous study, we established an efficient method for large-scale expansion of NK cells from healthy donors under GMP conditions for 2 weeks (12). We also completed a phase I clinical trial for solid tumor patients, administering NK cells produced from the 2 week-manufacturing process (11). However, the expansion of NK cells by the 2 wk-manufacturing process was limited in terms of the number of NK cells in the final products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we established an efficient method for large-scale expansion of NK cells from healthy donors under GMP conditions for 2 weeks (12). We also completed a phase I clinical trial for solid tumor patients, administering NK cells produced from the 2 week-manufacturing process (11). However, the expansion of NK cells by the 2 wk-manufacturing process was limited in terms of the number of NK cells in the final products.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials using ex vivo -expanded allogeneic NK cells have been performed in patients with advanced non-small cell lung cancer (phase I) and recurrent ovarian or breast cancers (phase II) (8910). Our group has also performed a phase I clinical trial with ex vivo -expanded allogeneic NK cells derived from random donors in patients with malignant lymphoma or advanced sold tumors (11). These studies have demonstrated the safety of allogeneic NK cell therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Though an antitumor effect of the adoptively transferred NK cells could be observed, their persistence in vivo was shorter (between 1 and 4 days) in comparison to other clinical trials. This stresses the potential need for an effective NK cell-promoting conditioning regimen, to increase the life span and migration of NK cells in patients (69). …”
Section: Adoptive Nk Cell Therapy In a Non-transplant Settingmentioning
confidence: 99%
“…Consistent with this observation, Yang et al recently demonstrated that activated allogeneic NK cell therapy can reduce the Treg population in peripheral blood. 38 Moreover, they demonstrated that adoptive NK therapy reduced not only Tregs, but also myeloid-derived suppressor cells (MDSC) in peripheral blood. These results suggest that ex vivo-activated NK cells have a novel role in overcoming the negative function of immune suppressor cells, through unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%